A Usage-Based Approach to Pattern Finding: The Traceback Method Meets Code-Mixing - Quick, Antje Endesfelder; Backus, Ad (Languages, 2022)
Usage-based approaches have become increasingly important in research on language acquisition and recently also in bilingual first language acquisition. Lexically specific patterns, such as What’s this? and frame-and-slot patterns, such as [I want X] play an important role in language acquisition scenarios. The ubiquity of such conventionalized chunks and frame-and-slot patterns supports the idea that children construct their early utterances out of concrete pieces they have heard and stored before. To investigate the emergence of patterns in children’s speech the traceback method has been developed, which accounts for the composition of utterances by relying on previously acquired material. Recently, the traceback method has also been applied to code-mixed utterances in bilingual children testing the assumption that bilingual utterances are structured around a frame-and-slot pattern in which the open slot is filled by (a) word(s) from the other language, e.g., [where is X] as in where is das feuer ‘where is the fire’. In this paper we want to present how the empirical use of the traceback method, and the general adoption of a usage-based theoretical perspective, can shed new lights on the study of bilingual phenomena, such as code-mixing.
CRIS-Team Scopus Importer:2022-11-17
Keywords: code-mixing; traceback method; usage-based